Just a Philomath, not a Polymath: Did the Paradigm of Integration-Interconnection of Sciences Obscure or Illuminate the Study of the Qur’an and Tafsir in Academic Institution? - Qadafy, Muammar Zayn; Yunita (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2025)
“You can blame me, that I started (the Integration-Interconnection of Science, hereinafter referred to as I-Con) from a theological (agenda), but my theology is not your theology. The difference (between them) is in the cross-reference of (sciences)”. This was Amin Abdullah’s response to a question addressed to him on whether the I-Con mega project is better regarded as an academic or theological agenda, a query that will always haunt it for years to come, as long as one still wonders if academic and theological studies to religious texts can swim in the same pool. This article is written to divulge some challenges and pitfalls in the mainstreaming of the I-Con paradigm for lecturers and students of the Qur’an and Tafsir Studies program in Indonesian Islamic Universities. Foremost is the nature of this paradigm as a reformist preaching orientated towards contextual-thematic interpretation, thus diverting the main attention of researchers in Qur’anic studies from uncovering many other important elements of the Qur’an. This article further argues that I-Con has significantly contributed to the establishment of what is referred to as the academic echolalia in applying foreign theories to tafsir studies, an oversight that should be rethought before it goes too far away.